Gaya Kepemimpinan Komunitas Anak Yatim dan Dhuafa dalam Kegiatan Open Donasi terhadap Masyarakat Desa Bandar Setia - Adelia Putri Zurianti; Sahrul Sahrul (Journal of Education on Social Science (JESS), 2023)
This study aims to find out how the leadership style is applied by the Community of Orphans and Dhuafa in open donation activities for village communities. This study used a qualitative approach with a descriptive research type. Research data was obtained from interviews, and observation. Data analysis techniques using data reduction, data presentation, and drawing conclusions. The results of this study indicate that the leadership style applied by the orphan and dhuafa community in carrying out open donation activities is a participatory leadership style. This participative leadership style invites all sections of the management to participate in carrying out the activities carried out. Give each other ideas and ideas to each other so as to create a benefit for fellow community administrators. Donations obtained by this community were obtained from donors and community cooperation with alms troops. With this community, orphans and poor people in Bandar Setia Village are more assisted both in terms of economy and education.